Ruptured Juxtarenal Abdominal Aortic Aneurysm Treated With a Fenestrated EVAR Graft Intended for a Different Patient. (August 2016) - Al-Jundi, Wissam; Elboushi, Amro; Lees, Tim; Williams, Robin
Treatment of juxtarenal abdominal aortic aneurysms (AAAs) remains challenging. A 79-year-old male who had infrarenal endovascular repair of abdominal aortic aneurysm (EVAR) 13 years previously presented with leaking juxtarenal AAA. Emergency fenestrated EVAR (FEVAR) was performed utilizing a stent graft designed and built for a different patient. Despite the need to embolize the celiac artery prior to covering it with the stent graft in order to achieve adequate proximal seal, the patient had uneventful recovery.